2022
DOI: 10.20961/lar.v20i3.58662
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh pemberian konsentrat pada waktu yang berbeda terhadap keberhasilan inseminasi buatan pada sapi Persilangan Limousin

Abstract: Penelitian ini bertujuan untuk mengevaluasi pengaruh dari pemberian konsentrat pada waktu yang berbeda terhadap keberhasilan inseminasi buatan pada sapi persilangan limousin. Metode: Metode penelitian yaitu eksperimental dilapang. Analisis data menggunakan Rancangan Acak Kelompok (RAK), pengelompokkan berdasarkan bobot badan (BB). Materi penelitian ini menggunakan sapi persilangan limousin sebanyak 45 ekor, masing-masing perlakuan 15 ekor, umur 1,5-6 tahun, BCS 4-6 (standar 1-9). Data yang diperoleh kemudian d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The non-return rate (NRR) is one of the methods used for estimating pregnancy success after insemination (Malda et al, 2022). Based on the research results shown in Table 1, it is known that the highest percentage of non-return rate 1 is T2, with a value of 95%, followed by T3, which is 82%, and T1, which is 76%.…”
Section: Percentage Of Non-return Ratementioning
confidence: 99%
“…The non-return rate (NRR) is one of the methods used for estimating pregnancy success after insemination (Malda et al, 2022). Based on the research results shown in Table 1, it is known that the highest percentage of non-return rate 1 is T2, with a value of 95%, followed by T3, which is 82%, and T1, which is 76%.…”
Section: Percentage Of Non-return Ratementioning
confidence: 99%
“…The low CR value can be caused by silent heat that occurs due to ovary hypofunction and ovary cystic follicles and feed consumption that cannot meet the daily needs of livestock. [34] explained that ovarian hypofunction is a condition where ovarian function decreases, so that there is no optimal follicular development caused by impaired secretion of FSH and LH hormones, while cystic follicles are young follicles that grow on the ovary for 10 days or more caused by a lack of LH hormones so that ovulation or anovular does not occur. [35] added that the ovum produced by ovary hypofunction has low fertility, making it difficult to fertilize even though the spermatozoa are of good quality.…”
Section: Artificial Insemination Success Based On Conception Ratementioning
confidence: 99%
“…Hormone synthesis in livestock will stimulate the stimulation of hormone secretion so that signs of estrus appear in livestock Bindari et al [9]. The nutritional content in feed needs to be considered to meet protein and energy needs for livestock production and reproduction Malda et al [10]. The concentrate is an additional necessary feed to supplement protein obtained from forage feed.…”
Section: Introductionmentioning
confidence: 99%